Social cognitive framework for secure information sharing on Islamic NGO social media / Nurul’Adilah Nazri - Nurul’Adilah , Nazri (2022)
The use of social media technologies such as Facebook, Twitter, Wikis, WhatsApp, and so forth is becoming a trend nowadays. Professionals often use social media in social work as an information and communication tool. Most profit organizations use this technology to help their business. Non-profit organizations are also known as non-governmental organizations (NGOs) also benefit in many aspects from using this technology. This research focused on Islamic NGOs which addressed education as one of their social missions. This research aims to achieve three main objectives; 1) to identify factors that influence secure information sharing practices of Islamic NGOs in spreading social mission using social media; 2) to develop social cognitive framework for secure information sharing by Islamic NGOs in spreading social mission using social media; and 3) to verify social cognitive framework for secure information sharing by Islamic NGO in spreading social mission using social media. A quantitative method was used in this research to find out the relationship between Personal/Cognitive, Behavior and Environmental determinants through Social Cognitive Theory. It started with data collection from 73 of NGO members to find out the usage of social media in the NGOs. The data were analyzed using structural equation modelling (Structural Equation Modelling (SEM)) technique using Partial Least Square (Partial Least Square (PLS)). The results show high reliability of predicted variables with reliability score of more than 0.80, displaying average variance extracted (Average Variance Extracted (AVE)) exceeding 0.5, define adequate convergent validity of all the predicted variables developed in the conceptual framework. It was found that from hypothesis 2, the behavioral determinant positively influences secure information sharing of Islamic NGOs through social media and from hypothesis 3, the environmental determinant positively influences secure information sharing of Islamic NGOs through social media. However, from hypothesis 1, it was found that personal/cognitive determinant does not positively influence secure information sharing of Islamic NGOs through social media. The social cognitive framework developed in this study shows the coefficient of determination (R2) is 0.584 which indicates the significance of predictive accuracy.